O Pewnej Metodzie Obliczania Amplitud Drgań Wymuszonych - Fiszdon, W. (Engineering Transactions, 1953)
The use of the admittance method for the determination of amplitudes of forced vibrations of deformable elastic systems with internal damping is described. This method enables to take into account the real elastic, inertial and damping characteristics of systems with many degrees of freedom thus giving the possibility of a more accurate calculation of forced amplitudes than in the usually employed methods. An approximate method using previous experience on similar systems is indicated. This method is particularly suitable for the determination of the best flexibility of the a suspension of a large mass on a flexible finite mass.